2006
DOI: 10.1093/biostatistics/kxl032
|View full text |Cite
|
Sign up to set email alerts
|

An informative Bayesian structural equation model to assess source-specific health effects of air pollution

Abstract: A primary objective of current air pollution research is the assessment of health effects related to specific sources of air particles or particulate matter (PM). Quantifying source-specific risk is a challenge because most PM health studies do not directly observe the contributions of the pollution sources themselves. Instead, given knowledge of the chemical characteristics of known sources, investigators infer pollution source contributions via a source apportionment or multivariate receptor analysis applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 28 publications
(43 reference statements)
0
50
0
Order By: Relevance
“…Although the potential advantages of SEMs have been touted for some time in the lead literature18 and have more recently gained traction in studies of mercury2 7 and PM air pollution,5 6 they have not yet gained widespread use in the field of occupational health. Nearly 25 years have passed since Bornschein et al first noted the value of these methods for dealing with complicated epidemiological questions, and a significantly longer period has passed since their widespread use in econometrics.…”
Section: Discussionmentioning
confidence: 99%
“…Although the potential advantages of SEMs have been touted for some time in the lead literature18 and have more recently gained traction in studies of mercury2 7 and PM air pollution,5 6 they have not yet gained widespread use in the field of occupational health. Nearly 25 years have passed since Bornschein et al first noted the value of these methods for dealing with complicated epidemiological questions, and a significantly longer period has passed since their widespread use in econometrics.…”
Section: Discussionmentioning
confidence: 99%
“…First, to identify the model, we constrained parameters in according to the C1-C3 identifiability conditions (Park et al, 2002) as defined in Equation (8). Nikolov et al (2007) found that zeroing out factor loading according to the C1-C3 identifiability conditions does not largely impact inference when the true factor loadings are low (not larger than 0.2). Based on the body of pre-existing work on Boston PM (Oh et al, 1997;Clarke et al, 2000;Batalha et al, 2002), we identified a subset of elements whose contribution by each source is expected to be minimal and constrained these loadings to zero.…”
Section: Simulation Studymentioning
confidence: 93%
“…Notably, the latent variables correspond to what is “common” among the parameters measured and do not preclude, for example, CRP and sVCAM-1 representing in part different biological processes. SEMs have been used in studies that assessed source-specific health effects of air pollution 9,10 and in health effects of methyl mercury 11 and lead to neurodevelopment. 12,13 Notably, SEMs reduce the attenuation due to measurement error in models with 3 or more surrogates of the latent exposure, 14 which is an ongoing concern in air pollution studies.…”
Section: Introductionmentioning
confidence: 99%